Mass spectrometric characterization of the selective androgen receptor modulator (SARM) YK‐11 for doping control purposes. (18th June 2017) - Thevis, Mario; Piper, Thomas; Dib, Josef; Lagojda, Andreas; Kühne, Dirk; Packschies, Lars; Geyer, Hans; Schänzer, Wilhelm
Abstract : Rationale: Selective androgen receptor modulators (SARMs) represent an emerging class of therapeutics targeting inter alia conditions referred to as cachexia and sarcopenia. Due to their anabolic properties, the use of SARMs is prohibited in sports as regulated by the World Anti‐Doping Agency (WADA), and doping control laboratories test for these anabolic agents in blood and urine. In order to accomplish and maintain comprehensive test methods, the characterization of new drug candidates is critical for efficient sports drug testing. Hence, in the present study the mass spectrometric properties of the SARM YK‐11 were investigated. Methods: YK‐11 was synthesized according to literature data and three different stable‐isotope‐labeled analogs were prepared to support the mass spectrometric studies. Using high‐resolution/high‐accuracy mass spectrometry following electrospray ionization as well as electron ionization, the dissociation pathways of YK‐11 were investigated, and characteristic features of its (product ion) mass spectra were elucidated. These studies were flanked by density functional theory (DFT) computation providing information on proton affinities of selected functional groups of the analyte. Results and Conclusions: The steroidal SARM YK‐11 was found to readily protonate under ESI conditions followed by substantial in‐source dissociation processes eliminating methanol, acetic acid methyl ester, and/or ketene. DFT computation yielded energetically favored structures of the protonated species resulting from the aforementioned elimination processes particularly following protonation of the steroidal D‐ring substituent. Underlying dissociation pathways were suggested, supported by stable‐isotope labeling of the analyte, and diagnostic product ions for the steroidal nucleus and the D‐ring substituent were identified. Further, trimethylsilylated YK‐11 and its deuterated analogs were subjected to electron ionization high‐resolution/high‐accuracy mass spectrometry, complementing the dataset characterizing this new SARM. The obtained fragment ions resulted primarily from A/B‐ and C/D‐ring structures of the steroidal nucleus, thus supporting future studies e.g. concerning metabolic pathways of the substance. Copyright © 2017 John Wiley & Sons, Ltd.